Early breast expression for very low birth infants admitted to neonatal intensive care unit: the challenges of cesarean deliveries. (12th December 2022) - Bin-Nun, Alona; Kassirer, Yair; Jarallah, Yousef; Barg, Moshe; Mimouni, Francis B.; Hammerman, Cathy; Sela, Hen Y.
Abstract: Aim of the study: In preterm infants, the use of human milk is associated with unique benefits. However, successful breast feeding rates and prolonged breastfeeding duration is often reduced in preterm infants. Nevertheless, early initiation of breast expression after birth is believed to be one of the major variables that should improve the odds of successful breastfeeding. Hence, we aimed to assess correlation between timing of milk expression initiation and volume produced in regards to mode-of-delivery. Materials and methods: Prospective, observational study. Mothers delivering infants weighing < 1500 g measured 24-h milk volumes on days 1–7, 14, and 21. Results: Mothers delivering vaginally ( N  = 11) expressed milk sooner (3.82 ± 5.03 h) than mothers in the cesarean group ( N  = 42; 11.5 ± 9.1 h). There were no significant differences in daily number of expressions (i.e. day 1 3.6 ± 1.6 versus 2.5 ± 2.1, p  = .125) or daily volume (i.e. day 1 – 7.5 ± 6.1 ml versus 11.6 ± 22.9 ml, p  = .563), until day 6 from which, both were lower in the cesarean group (i.e. day 21 – number − 6.0 ± 1.3 versus 4.6 ± 1.7, p  = .029; volume – 796 ± 465ml versus 435 ± 368ml, p  = .018). Expressed volume initially did not correlate with earlier expression, however, latter expressed volume inversely correlated with earlier expression. In multivariate-analysis, mode of delivery, gestational age, and daily number of expressions were correlated with volumes on day 21 ( p  = .001). Conclusions: Earlier human-milk expression is related to volumes on the second and the third week of lactation. This is overwhelmed by delivery mode, and by frequent milk expression from day 2. When early milk expression is not possible, more frequent milk expression might help increasing volumes.